Longitudinal impact of interactive science activities: Developing, implementing, and validating a graphing integration inventory - Boda, Phillip A.; Bathia, Shruti; Linn, Marcia C. (Journal of research in science teaching, 2021)
Integrating sophisticated graphical analysis skills as they learn science is essential for K‐12 students and emphasized in current standards. In this study, we iteratively designed a Graphing Integration Inventory (GII) over a three‐year period, while also supporting students to develop their capabilities to use graphs to learn science content in complex ways through interactive curriculum materials implemented on a novel technology enhanced curriculum platform. We applied the Knowledge Integration framework to design the curriculum, the assessments, and the rubrics for scoring student explanations. The framework delineates ways to promote links among graphs and science ideas. The rubrics award students higher scores on their explanations based on the level of complexity of their connections between science concepts and, in this research, graphs. The GII and the aligned curriculum were implemented by over 300 middle school students (Grades 6–8) across a 3‐year period. We investigated the impact of the designed curriculum on the integration of graphing and science while also studying the psychometric properties of the GII to validate it for use in future studies. Findings suggest both that the curriculum used to support these students improved their Knowledge Integration capabilities significantly and that the GII instrument is suitable for use with populations across gender and native English language status demographics in Grades 6–8. Implications are discussed around using graphs to learn complex science ideas, as well as the affordances of technology enhanced platforms to support this type of learning and assessment.